ANALISIS KANDUNGAN UNSUR HARA DAN KUALITAS FISIK LIMBAH PADAT BIOGAS DENGAN BAHAN BAKU EMPAT JENIS SAMPAH SAYURAN - Euis Yulianingsih; Danang Biyatmoko; Djodjok Rahardjo; Lusita Wardani (Universitas Lambung Mangkurat, 2011)
The objectives of this research were to find out: (1) nutrient content N, P, K of biogas solid waste, (2) C/N ratio of biogas solid waste and (3) physical quality of biogas solid waste consisted of colour, odor, texture and fungi. The research was conducted in Environmental Health of POLTEKES Banjarmasin from March until July 2009. The research used Kruskall Wallis analysis and its experimental design was Completely Randomized Design with four treatments of different material of biogas. Its treatments were material of biogas of mustard vegetable garbage, material of biogas of cabbage vegetable garbage, material of biogas of kangkung vegetable garbage and material of biogas of cassava vegetable garbage. The result of nutrient content analysis indicated that the highest nutrient content of Nitrogen was at material of biogas of cassava vegetable garbage that was 2.91%. The highest nutrient content of Phosfor was at material of biogas of mustard vegetable garbage was 18.38%. The highest nutrient content of Kalium was at material of biogas of mustard vegetable garbage was 1.94% and the best C/N ratio was at material of biogas of cassava vegetable garbage was 17.09. The result of physical quality analysis of biogas solid waste i.e odor, colour, texture and fungi. In odor parameter, materials of biogas of mustard and cassava vegetable garbage has scoring value 3.00 that was odorous. In colour parameter, materials of biogas of mustard and cabbage vegetable garbage has scoring value 3.00 its means at the treatments has brown colour, like land colour. In texture parameter, materials of biogas of mustard and cabbage vegetable garbage has scoring value coming near scoring value 2.00 that was harsh texture, meanwhile materials of biogas of kangkung and cassava vegetable garbage has scoring value 1.00 its means has clotty texture. In fungi parameter, materias of biogas of mustard and cabbage vegetable garbage has scoring value 3.00 its means no one fungi in the treatments.